Gradations in digital inclusion : children, young people and the digital divide - Livingstone, Sonia; Helsper, Ellen (New Media and Society, 2007)
Little academic and policy attention has addressed the ‘digital divide’ among children and young people. This article analyses findings from a national survey of UK 9-19 year olds that reveal inequalities by age, gender and socioeconomic status in relation to their quality of access to and use of the internet. Since both the extent of use and the reasons for low and non-use of the internet vary by age, a different explanation for the digital divide is required for children compared with adults. Looking beyond the idea of a binary divide, we propose instead a continuum of digital inclusion. Gradations in frequency of internet use (from non and low users through to weekly and daily users) are found to map onto a progression in the take-up of online opportunities among young people (from basic through moderate to broad and then all-round users), thus beginning to explain why differences in internet use matter, contributing to inclusion and exclusion. Demographic, use and expertise variables are all shown to play a role in accounting for variations in the breadth and depth of internet use.
Keywords: digital divide; digital inclusion; internet; jeunesse